Redesain Tata Letak Pabrik Gula dalam Meningkatkan Efesiensi dan Produktivitas CV. Rizki Abadi - Pascal Sidqi Lubis; Hilda Ayu Retno Nur Fitria Dewi; Evi Selvi (Universitas Batanghari, 2022)
This study aims to improve the layout of CV Rizki Abadi's production facilities so as to increase efficiency and productivity. Redesign of the company needs to be done because consumer demand is often not met until it reaches 64.5 tons in 2020. This study only discusses material handling costs, productivity percentages, and the layout improvement model chosen by the factory owner from the three models proposed by the researcher. The layout analysis in this study uses the CRAFT algorithm. The CRAFT algorithm can provide the best layout improvement model output after exchanging the location of the facilities. The analysis shows that the total cost of material handling in the initial layout is Rp. 2,950,838. After repairs were made using the CRAFT algorithm and approved by the factory owner (model 3) by exchanging facilities between Work Station 3 (Draining) and Work Station 2 (Mold Stacking), material handling costs were more efficient to only Rp. 1,257,115.5 or 2 ,25%. Initial layout productivity also increased from 14.27% to 16.6%.